Self-efficacy, Career Commitment, and Training Transfer Among Millennials - Oliandes Sondakh (Journal of Enterprise and Development (JED), 2024)
Purpose: This research examines the effect of self-efficacy on the transfer of training, with career commitment as a moderating variable, focusing on Millennials.Method: The study employs a quantitative research method conducted in Indonesia’s three largest metropolitan areas: Jakarta, Surabaya, and Bandung. Data were collected directly from primary sources using questionnaires distributed to 100 selected respondents. Responses were measured on a five-point Likert scale. The sampling technique applied was non-probability sampling with a purposive method. The collected data were analyzed using statistical Partial Least Squares (PLS).Result: The findings reveal that self-efficacy significantly affects both career commitment and the transfer of training in both Gen Y.1 and Gen Y.2. Interestingly, the effect of career commitment on the transfer of training varies between the two groups. Among Gen Y.2, career commitment significantly impacts the transfer of training. However, in Gen Y.1, career commitment, while showing a positive trend, does not have a statistically significant effect on the transfer of training.Novelty: While previous research has explored factors influencing training transfer, this study introduces a novel perspective by focusing specifically on Millennials, who represent Indonesia's dominant workforce. It highlights the unique generational characteristics of Generation Y and their impact on training effectiveness. This focus is particularly relevant as Millennials are poised to drive Indonesia’s economic growth by 2030.